Breaking dawn - Meyer, Stephenie, 1973- (New York : Little, Brown and Co., 2008)
Although eighteen-year-old Bella joins the dark but seductive world of the immortals by marrying Edward the vampire, her connection to the powerful werewolf Jacob remains unsevered.
*Strictly for G7 students and above level use only
Keywords: Vampires; Werewolves; Interpersonal relations